A multi-head attention network with adaptive meta-transfer learning for RUL prediction of rocket engines. (September 2022) - Pan, Tongyang; Chen, Jinglong; Ye, Zhisheng; Li, Aimin
Abstract: Accurate prediction of remaining useful life (RUL) is necessary to ensure stable and safe operations for rocket engines. The paper proposed a multi-head attention network coupled with adaptive meta-transfer learning for RUL prediction. By combining the convolution-based branch with an attention-based branch, the multi-head attention network is proposed for accurate RUL prediction of cryogenic bearings in rocket engines under the steady stage. In addition, an adaptive model-agnostic meta-transfer learning strategy is developed to further improve the performance under small sample circumstances with adaptive hyper-parameters. To demonstrate the superiority, the proposed method is compared with typical benchmark algorithms using real monitoring data from a high-precision cryogenic rocket engine experiment platform. Results indicate that the proposed method achieves better performance compared with existing models under multiple evaluation indexes. Highlights: A multi-head attention network with dual branches is proposed for RUL prediction. A coupling unit is designed to complete dimension alignment for two branches. An adaptive meta-transfer learning strategy is proposed for knowledge transfer. We built a cryogenic experiment platform in liquid nitrogen for verification.